Comparison of 2D vena contracta area with 3D planimetric mitral valve area in rheumatoid mitral valve disease - (:unkn) unknown (SPRINGER, 2020)
Rheumatoid valve disease is a general health problem of developing countries, and it mainly affects after the age of 40. Assessment of the correct mitral valve area (MVA) is important for the treatment of rheumatoid valve disease. However, there are contradictions between the three-dimensional (3D) and two-dimensional (2D) methods. A measurement with 3D echocardiography is a more accurate method to measure the MVA. However, in centers without 3D echocardiography, there are some difficulties in the accurate measurement of the MVA. The aim of this study was to assess the value of 2D transesophageal echocardiography (TEE) mitral valve vena contracta area (VCA) in predicting the severity of rheumatoid mitral stenosis (RMS) by comparing 3D planimetry. A total of 24 patients (10 females and 14 males) who were diagnosed with mild/moderate/severe RMS with using pressure half time, mean transmitral gradient, and planimetry methods were included in this study. 3D images were acquired using the 3D zoom and full volume. 2D TEE VCA was measured at an angle of 140 degrees and 60 degrees, which was perpendicular to the former, with color Doppler and the VCA was measured with an ellipsoid area using mathematical formula. There was statistically significant relationship between the measurements of 2D VCA and 3D zoom mode MVA planimetry and MVA full measurements (MVA full volume) (p < 0.01). Calculation of the valvular area after measuring the mitral valve VCA with 2D TEE is a reliable method that is usable in centers without 3D echocardiography.
Keywords: 3D-Echocardiography; Mitral stenosis; Transesophageal echocardiogrpahy; TRANSESOPHAGEAL ECHOCARDIOGRAPHY; STENOSIS; SEVERITY